Development and Validation of 58K SNP-Array and High-Density Linkage Map in Nile Tilapia (O. niloticus) - Joshi, Rajesh; Árnyasi, Mariann; Lien, Sigbjørn; Gjøen, Hans Magnus; Alvarez, Alejandro Tola; Kent, Matthew (Frontiers in Genetics, 2018)
Despite being the second most important aquaculture species in the world accounting for 7.4% of global production in 2015, tilapia aquaculture has lacked genomic tools like SNP-arrays and high-density linkage maps to improve selection accuracy and accelerate genetic progress. In this paper we describe the development of a genotyping array containing more than 58,000 SNPs for Nile tilapia (Oreochromis niloticus). SNPs were identified from whole genome resequencing of 32 individuals from the commercial population of the Genomar strain, and selected for the SNP-array based on polymorphic information content and physical distribution across the genome using the Orenil1.1 genome assembly as reference sequence. SNP-performance was evaluated by genotyping 4991 individuals, including 689 offspring belonging to 41 full-sib families, which revealed high-quality genotype data for 43,588 of the SNPs. A preliminary genetic linkage map was constructed using Lepmap2 which in turn was integrated with information from the O_niloticus_UMD1 genome assembly to produce an integrated physical and genetic linkage map comprising 40,186 SNPs distributed across 22 linkage groups. Around one-third of the linkage groups showed a different recombination rate between sexes, with male and female map lengths differing by a factor of 1.2 (1359.6cM and 1632.9cM respectively), with most linkage groups displayed a sigmoid recombination profile. Finally, the sex-determining locus in this population was mapped to position 40.53 cM on linkage group 23, in the vicinity of the anti-Müllerian hormone (amh) gene. These new resources has the potential to greatly influence and improve the genetic gain when applying genomic selection and surpass the difficulties of efficient selection for invasive traits in tilapia.